1996
DOI: 10.1152/jappl.1996.80.4.1279
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared estimation of O2 supply and consumption in forearm muscles working at varying intensity

Abstract: We estimated a blood flow index, O2 supply index, and O2 consumption index from near-infrared (NIR) signals during venous occlusion imposed at rest and immediately after handgrip exercise with loads equal to 5, 10, 15, 20, 25, and 30% of the maximum voluntary contraction. We also estimated forearm blood flow (BFfa) by strain-gauge plethysmography and forearm O2 consumption (VO2fa) by the invasive method. There was a significant correlation between the rate of increase in total hemoglobin during venous occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 0 publications
1
91
0
2
Order By: Relevance
“…The measurement is intermittent and yields one value per venous occlusion. However, the values are likely to be reproducible even if measured on different days (44,50). The spatial resolution is on the order of 1 cm and is two-dimensional.…”
Section: Limitations Potential Clinical Applications and Outlookmentioning
confidence: 97%
See 1 more Smart Citation
“…The measurement is intermittent and yields one value per venous occlusion. However, the values are likely to be reproducible even if measured on different days (44,50). The spatial resolution is on the order of 1 cm and is two-dimensional.…”
Section: Limitations Potential Clinical Applications and Outlookmentioning
confidence: 97%
“…The measurements of SvO 2 (49) and blood flow (35,50) have also been validated against other methods.…”
Section: Precision and Trvmentioning
confidence: 99%
“…A previous study on stimulated canine muscle showed that intramuscular pressure gradient from the distal to the proximal portion of muscle was a major driving force pushing blood out of the muscle [5]. Homma et al [24] reported that NIR-blood volume determined by the ischemia technique could reflect blood flow. The index of NIR-blood volume should be sensitive to changes in intramuscular pressure, with increasing intramuscular pressure decreasing blood volume.…”
Section: Fig 3 Typical Changes For Nir-o 2 Saturation (Top)mentioning
confidence: 99%
“…However, blood sampling is invasive and requires a high precision. The widely used indirect measure of muscle blood flow is strain-gauge plethysmography 21,32,33) . However, with this method, it is impossible to measure absolute values (i.e., ml/min/100 g tissue) during moderate to strenuous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The reducibility of forearm blood flow during rest using the venous occlusion method has proved to be reliable within test sessions, although the mean values of the within-subject variability varied by between 10 and 29% 21,23,24) . NIRS blood flows for resting and post-exercise s h o w g o o d a g r e e m e n t w i t h s t r a i n -g a u g e plethysmography 21,32) , although flow measured by plethysmography is generally two to three times higher than the NIRS flow 21,24) . On the other hand, VO 2NIRS using arterial occlusion can be calculated from the rate of decrease in OxyHb [37][38][39][40] or from the rate of decrease in Hbdiff, reflecting the difference between oxyand deoxyhaemoglobin (Hbdiff) 2 0, 22 -2 4, 37 ) .…”
Section: Discussionmentioning
confidence: 99%